Web-based Dementia Care Monitoring System - Soon Ning, Kew; Hafit, Hanayanti (Applied Information Technology And Computer Science, 2025)
Dementia is a condition where an individual progressively loses their cognitive functions until it is enough to interfere with their daily life. The spike in the aging population has caused this condition to be diagnosed mainly in the elderly. Professional caregivers are usually employed to take care of dementia individuals. However, caregivers alone are not able to care for and keep an eye on the well-being of dementia individuals all the time. This causes dementia individuals to wander off alone or unintentionally hurt themselves. One problem in caring for dementia individuals is the expensive technological devices and monitoring software. Nursing homes and non-profit organizations could not afford these technology devices and software in their services for monitoring dementia individuals. Another problem is the privacy and confidentiality of data. Data of dementia individuals and their family members are vulnerable to the exploitation of unwanted third parties. Therefore, a web-based dementia care monitoring system is proposed to be developed to keep track of the weekly or monthly activities of dementia individuals. Additionally, the journaling and photo album feature can help caregivers maintain the mental health of dementia individuals by giving them a space to express themselves. The development of the system follows the cycle of the Prototype Model. In contrast, the design of features, functionality, and flow of the system is done through wireframes and diagrams like DFD and ERD. Programming languages such as C# language and SQL server databases are used in the development process. Multiple tests on the system's functionalities have proven that the system manages to meet all users' requirements. The development of the web-based dementia care monitoring system ensures caregivers can provide a conducive environment for dementia individuals to carry out their daily activities.